2018
DOI: 10.1002/jcp.26458
|View full text |Cite
|
Sign up to set email alerts
|

Dehydroepiandrosterone rehabilitate BRL‐3A cells oxidative stress damage induced by hydrogen peroxide

Abstract: This study aimed to investigate the molecular mechanism of dehydroepiandrosterone (DHEA) rehabilitated BRL-3A cells oxidative stress damage induced by hydrogen peroxide (H O ). Results showed that DHEA reversed the decrease of cell viability and ameliorated nuclear chromatin damage in H O -induced BRL-3A cells. DHEA increased the activities of superoxide dismutase, catalase, peroxidase, and glutathione peroxidase, and decreased the reactive oxygen species (ROS) production in H O -induced BRL-3A cells. DHEA att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 42 publications
1
6
0
Order By: Relevance
“…Taken together, these results showed that phlorizin decreased the cell apoptosis by downregulating the expression of Caspase 3 and Caspase 9 genes and upregulating the expression of Bcl‐2 gene. This phenomenon was similar to that in a previous study ( Li, Zhao, et al, ), which stated that dehydroepiandrosterone relieves oxidative damage by decreasing the expression of apoptosis genes and increasing the expression of anti‐apoptosis gene in H 2 O 2 ‐induced BRL‐3A cells.…”
Section: Discussionsupporting
confidence: 91%
“…Taken together, these results showed that phlorizin decreased the cell apoptosis by downregulating the expression of Caspase 3 and Caspase 9 genes and upregulating the expression of Bcl‐2 gene. This phenomenon was similar to that in a previous study ( Li, Zhao, et al, ), which stated that dehydroepiandrosterone relieves oxidative damage by decreasing the expression of apoptosis genes and increasing the expression of anti‐apoptosis gene in H 2 O 2 ‐induced BRL‐3A cells.…”
Section: Discussionsupporting
confidence: 91%
“…In order to simulate oxidative injury in vascular endothelial cells in vivo, many oxidative stress models of endothelial cells have been established. H 2 O 2 ‐induced oxidative stress is well established as a common model for oxidative injury (Kaczara et al, ; Li, Zhao, Ge, Yu, & Ma, ). In the present study, apoptosis of HUVECs showed a dose‐dependent relationship with H 2 O 2 .…”
Section: Discussionmentioning
confidence: 99%
“…BRL-3A cells were pretreated with vehicle, 10 μ M Trilostane, 10 μ M Flutamide, or 1 μ M Fulvestrant for 60 min. The cells were then treated with DHEA (0, 1, 10, or 100 μ M), testosterone (12.0 nM), or estradiol (6.3 nM) for 24 h and subsequently treated with 150 μ M H 2 O 2 for another 2 h. Intracellular ROS content was analyzed with the fluoroprobe 2′,7′-dichlorodihydrofluorescein diacetate (H2DCF-DA) and dihydroethidium (DHE) as shown in our recent reports [16, 17]. Briefly, BRL-3A cells were incubated with H2DCF-DA for 30 min at 37°C, washed three times, and resuspended in cold PBS, after which they were immediately subjected to flow cytometry analysis with FACSCalibur™ (Becton Dickinson, San Jose, USA).…”
Section: Methodsmentioning
confidence: 99%
“…The cell treatments were the same as described in Section 2.4 for ROS analysis, and cell apoptosis was examined as reported in our studies [16, 17]. Briefly, BRL-3A cells were collected and washed with cold PBS, placed in 195 μ L Annexin V-FITC binding solution, incubated in 5 μ L Annexin V-FITC and 10 μ L propidium iodide in the dark for 30 min, and immediately subjected to flow cytometry analysis with FACSCalibur™.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation